Exploring stroke survivor experience of participation in an enriched environment: a qualitative study. (10th March 2015) - White, Jennifer H.; Bartley, Emma; Janssen, Heidi; Jordan, Louise-Anne; Spratt, Neil
Abstract: Background : Data highlight the importance of undertaking intense and frequent repetition of activities within stroke rehabilitation to maximise recovery. An enriched environment (EE) provides a medium in which these activities can be performed and enhanced recovery achieved. An EE has been shown to promote neuroplasticity in animal models of stroke, facilitating enhanced recovery of motor and cognitive function. However, the benefit of enriching the environment of stroke survivors remains unknown. Aim : To qualitatively explore stroke survivors' experience of implementation of exposure to an EE within a typical stroke rehabilitation setting, in order to identify facilitators and barriers to participation. Methods: Semi-structured interviews with 10 stroke survivors (7 females and 3 males, mean age of 70.5 years) exposed to an EE for a 2-week period following exposure to routine rehabilitation within a stroke rehabilitation ward. An inductive thematic approach was utilised to collect and analyse data. Results : Qualitative themes emerged concerning the environmental enrichment paradigm including: (1) "It got me moving" – perceived benefits of participation in an EE; (2) "You can be bored or you can be busy." – Attenuating factors influencing participation in an EE; (3) "I don't like to make the staff busier" – limitations to use of the EE. Conclusions : This study provides preliminary support for the implementation of an EE within a typical stroke rehabilitation setting from a patient perspective. Reported benefits included (1) increased motor, cognitive and sensory stimulation, (2) increased social interaction, (3) alleviation of degree of boredom and (4) increased feelings of personal control. However, participants also identified a number of barriers affecting implementation of the EE. We have previously published findings on perceptions of nursing staff working with stroke survivors in this enriched rehabilitation environment who identified that patients benefited from having better access to physical, cognitive and social activities. Together, results contribute to valuable evidence for future implementation of an EE in stroke rehabilitation settings. Implications for Rehabilitation: Stroke survivor access to an enriched environment (EE): Results identified that participation in both individual and communal forms of environment enrichment within the stroke rehabilitation ward resulted in increased access to activities providing increased opportunities for enhanced motor, cognitive and sensory stimulation. Increased access to and participation in activities of the environmental enrichment (individual and communal) interrupted the ongoing cycle of boredom and inactivity experienced by many participants. This study provides preliminary support for the implementation of an EE within a typical stroke rehabilitation setting from a patient perspective.